Decision Making Processes Under Uncertainties: Evaluating Discounted Cash Flow (DCF) and Real Option Valution Methods in Producing Better Investment Decision for Gas Project Development - Agung Nugroho, Putut; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2017)
Abstract. Oil & Gas Companies trying to manage shareholder values in a dynamic uncertain environments (Volatility of CAPEX, OPEX, Extractable reserves, Oil Gas Price, and External factors). Conventional valuation method on Capital Budgeting using Discounted Cash Flow (DCF) analysis as a base case (mindset of deterministic/ not changing futures) considered having a drawbacks in valuing projects under uncertainty. The gas project development is threatening not to be undertaken due to the raise the level of related tangible uncertainty factors (CAPEX, OPEX, Extractable reserves, Oil Gas Price, and other External factors) that not accommodated using base case of DCF analysis with constant discount rate. In another side, the project having vast multiplier effects that will empower the community in the area of the gas project. Another perspective of valuation method is needed to give another information for decision makers. Methodology-used in this final project is DCF analysis accommodating the uncertainty, using continuous DCF method with the calculation of Sensitivity analysis, the Scenario Analysis and the Monte Carlo Analysis. Real Options valuation will be calculate from Black, Scholes, and Merton formula of European financial options valuation, and using binomial lattice option methodology. Project valuation with DCF base analysis up to continuous method of Monte Carlo analysis, showing that the Net Present Value (NPV) is relatively have variance smaller of US$M 1267 toward to project valuation using Real Option. Project valuation using Real Options, may lead to unprofitable projects being undertaken. Project valuation using DCF analysis may lead to profitable project is not undertaken. Development of a hybrid, or methods that combine DCF and Real Options, may contribute in better decision making processes of project valuation under uncertainty.Key word: Uncertainty factor, Project Valuation, NPV, DCF, Real Options, Decision making process